2019
DOI: 10.1002/ana.25467
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy improves brain white matter in aromatic l‐amino acid decarboxylase deficiency

Abstract: Objective: Children with aromatic L-amino acid decarboxylase (AADC) deficiency suffer from severe motor dysfunction. Restoration of dopamine levels in the putamen by gene therapy has led to significant improvement in motor function. This study explored brain structure changes in patients. Methods: Brain diffusion tensor imaging (DTI) was performed before and 12 months after gene therapy. Whole-brain tract-specific analysis was performed to assess white matter microstructural integrity. Results: In the 8 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
(108 reference statements)
0
27
0
Order By: Relevance
“…Once the estimated duty cycle was under 40%, DTI imaging parameters we set were acceptable to scan rodent brains. The diffusion MRI data was acquired using a single-shot spin-echo echo-planar-imaging sequence with following parameters: TR/TE = 6750 ms/34.5 ms, FOV = 20 × 20 mm 2 , matrix = 75 × 75, 22 axial slices with 0.267 mm thickness, averages = 10, flip angle = 90°, in-plane resolution = 267 × 267 μm 2 , b-values for 42 diffusion gradient directions (1 b0/41 directions) = 0/1000 s/mm 2 , diffusion gradient duration (δ) = 2.112 ms; diffusion gradient separation (Δ) = 25.699 ms 31 . To quantify the thickness of the corpus callosum, we measured the thickness of the genu at the midline on one axial slice that best delineated the genu.…”
Section: Methodsmentioning
confidence: 99%
“…Once the estimated duty cycle was under 40%, DTI imaging parameters we set were acceptable to scan rodent brains. The diffusion MRI data was acquired using a single-shot spin-echo echo-planar-imaging sequence with following parameters: TR/TE = 6750 ms/34.5 ms, FOV = 20 × 20 mm 2 , matrix = 75 × 75, 22 axial slices with 0.267 mm thickness, averages = 10, flip angle = 90°, in-plane resolution = 267 × 267 μm 2 , b-values for 42 diffusion gradient directions (1 b0/41 directions) = 0/1000 s/mm 2 , diffusion gradient duration (δ) = 2.112 ms; diffusion gradient separation (Δ) = 25.699 ms 31 . To quantify the thickness of the corpus callosum, we measured the thickness of the genu at the midline on one axial slice that best delineated the genu.…”
Section: Methodsmentioning
confidence: 99%
“…Keeping up to date with the emergence of new gene therapies is essential. Gene therapy trials using viral vectors results in improvement of MD and motor function in early clinical studies of AADC deficiency (150,151). Kojima et al, conducted an open-label phase 1/2 study including six patients whom received adeno-associated virus vector harboring DDC via bilateral intraputaminal infusions.…”
Section: Step 5 Treatment Of Pediatric Metabolic Movement Disordersmentioning
confidence: 99%
“…As an adverse effect, transient chorea was observed (150). Tseng et al, demonstrated that there was an improvement in the microstructural integrity of white matter tracts using Brain diffusion tensor imaging (DTI) 1 year after AADC gene therapy (151).…”
Section: Step 5 Treatment Of Pediatric Metabolic Movement Disordersmentioning
confidence: 99%
“…The International Working Group on Neurotransmitter related Disorders (iNTD) published a consensus guideline on drug treatment recommendations for AADC deficiency; nevertheless, treatment options are not considered as disease‐changing . Recent clinical trials evaluating DDC gene replacement therapy using an adeno‐associated virus vector (AAV2‐hAADC) bilaterally administered to the putamen or substantia nigra showed sustained improvement of motor and cognitive functions and accompanying neuroradiologic and neurometabolic changes . Positive treatment outcomes correlated with early, pre‐symptomatic diagnosis and treatment initiation, emphasising the need for early and reliable diagnostic approaches, for example, in newborn screening (NBS) .…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Recent clinical trials evaluating DDC gene replacement therapy using an adeno-associated virus vector (AAV2-hAADC) bilaterally administered to the putamen or substantia nigra showed sustained improvement of motor and cognitive functions and accompanying neuroradiologic and neurometabolic changes. [5][6][7] Positive treatment outcomes correlated with early, pre-symptomatic diagnosis and treatment initiation, emphasising the need for early and reliable diagnostic approaches, for example, in newborn screening (NBS). 6,7 3-OMD concentration is increased in dried blood spots of AADC deficient patients, and hence is a candidate biomarker for NBS.…”
Section: Introductionmentioning
confidence: 99%